Export subsidies after Nairobi - Illescas, Nelson (2017)
The first provision on export subsidies appeared in the first paragraph of Article XVI of The General Agreement on Tariffs and Trade of 1947 (GATT). The paragraph mainly established an obligation to notify the contracting parties, which provided the possibility to discuss the effect of the subsidization and, in the event of prejudice or threat, evaluate the possibility of limiting said subsidization.